Evaluasi Kinerja dan Pengembangan Model Kelembagaan Lembaga Pengawasan Daerah - Hidayat, Dayat (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2008)
The regulation of The Regional Financial No 17/2003 says, that the management of the public finance is based on the performance budgeting principal. Its means that the allocation of the budget is a part of the governmental management. The performance it self is measured by the standard of performance that consist of input, output, outcomes, benefit and impact performance. So that, the measurement of performance is very important as a basis of accountability to the society as a services achievement.